"All one in Christ Jesus"? Spiritual closeness, genealogical determinism and the conversion of Jews in Alonso de Espina's Fortalitium Fidei. (2nd July 2016) - Soyer, François
ABSTRACT: Alonso de Espina's vitriolic polemic, Fortalitium Fidei (The fortress of faith, c. 1458–1464), includes a ferocious attack upon both Jews and the descendants of converts, who were collectively accused of judaizing. This would seem to set him at odds with the Apostle Paul's formulation in Galatians 3:28 of a powerful notion of equality between Christians that transcended ethnic divisions. Espina has become notorious among modern historians as an influential "anti-Semitic" writer. In this article, I argue that the significance of Espina's opus for the wider history of anti-Jewish texts needs to be revised and nuanced since, in stark contrast to many later anti- converso polemicists, he does not seek to undermine the Pauline concept of Christian spiritual closeness by appealing to biological or genealogical determinism; rather, he insists on the generalization of converso judaizing and the exceptionality of genuine Jewish conversions to Christianity.